2016
DOI: 10.1136/bmj.i4189
|View full text |Cite
|
Sign up to set email alerts
|

Association between payments from manufacturers of pharmaceuticals to physicians and regional prescribing: cross sectional ecological study

Abstract: Objective To examine the association between payments made by the manufacturers of pharmaceuticals to physicians and prescribing by physicians within hospital referral regions.Design Cross sectional analysis of 2013 and 2014 Open Payments and Medicare Part D prescribing data for two classes of commonly prescribed, commonly marketed drugs: oral anticoagulants and non-insulin diabetes drugs, overall and stratified by physician and payment type.Setting 306 hospital referral regions, United States.Participants 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 28 publications
7
110
1
1
Order By: Relevance
“…A growing body of work suggests that detailing has a significance influence on physician prescribing behavior (Fleischman et al, 2016). This is why, of course, the pharmaceutical industry spends billions of dollars a year on detailing.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work suggests that detailing has a significance influence on physician prescribing behavior (Fleischman et al, 2016). This is why, of course, the pharmaceutical industry spends billions of dollars a year on detailing.…”
Section: Discussionmentioning
confidence: 99%
“…They find increased rates of prescribing among those who received a meal promoting the drug interest. Fleischman et al perform a cross sectional analysis of hospital referral regions with 2013‐2014 OPD and Medicare Part D prescriptions for two drug classes. They find that transfers are associated with increased rates of prescribing.…”
Section: Existing Literaturementioning
confidence: 99%
“…Increased contact with and payment from industries may lead to increased physician loyalty to particular brands of new technologies and manifest itself as increased utilization of industry products. Several studies have demonstrated that increasing usage of new medications and technologies is associated with increasing industry payments across medical subspecialties . Particularly for new technologies such as BD, close contact with industry representatives may be required to better understand and apply the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that increasing usage of new medications and technologies is associated with increasing industry payments across medical subspecialties. [12][13][14] Particularly for new technologies such as BD, close contact with industry representatives may be required to better understand and apply the technology. Credentialing courses are sponsored by BD companies, and industry representatives have frequent contact with physicians who are utilizing BD both inside and outside of the operating room.…”
Section: Introductionmentioning
confidence: 99%